African Americans with translocation t(11;14) have superior survival after autologous hematopoietic cell transplantation for multiple myeloma in comparison with Whites in the United States. Issue 1 (23rd September 2020) - Badar, Talha; Hari, Parameswaran; Dávila, Omar; Fraser, Raphael; Wirk, Baldeep; Dhakal, Binod; Freytes, Cesar O.; Rodriguez Valdes, Cesar; Lee, Cindy; Vesole, David H.; Malek, Ehsan; Hildebrandt, Gerhard C.; et al.
Abstract : Background: Multiple myeloma (MM) with the translocation t(11;14) may have inferior outcomes in comparison with other standard‐risk MM, and it has been suggested to portend a worse prognosis in African Americans in comparison with Whites. This study used the Center for International Blood and Marrow Transplant Research (CIBMTR) database to examine the impact of t(11;14) on the clinical outcomes of patients with MM of African American and White descent. Methods: This study evaluated 3538 patients who underwent autologous hematopoietic cell transplantation (autoHCT) for MM from 2008 to 2016 and were reported to the CIBMTR. Patients were analyzed in 4 groups: African Americans with t(11;14) (n = 117), African Americans without t(11;14) (n = 968), Whites with t(11;14) (n = 266), and Whites without t(11;14) (n = 2187). Results: African Americans with t(11;14) were younger, had lower Karnofsky scores, and had more advanced stage MM with a higher Hematopoietic Cell Transplantation–Comorbidity Index (HCT‐CI). Fewer African Americans with t(11;14) (21%) had a coexistent high‐risk marker in comparison with Whites with t(11;14) (27%). In a multivariate analysis, race and t(11;14) had no association with progression‐free survival. However, overall survival was superior among African Americans with t(11;14) in comparison with Whites with t(11;14) (hazard ratio, 0.53; 95% confidence interval, 0.30‐0.93; P = .03). Survival was also associated with female sex, stage, time from diagnosis to transplant, a low HCT‐CI, and receipt of maintenance. Conclusions: Race may have a differential impact on the survival of patients with t(11;14) MM who undergo autoHCT and needs to be further studied. Abstract : Race has a differential impact on the survival of patients with translocation t(11;14) multiple myeloma who undergo autologous hematopoietic cell transplantation. African Americans with t(11;14) have superior survival in comparison with Whites after adjustments for other prognostic factors.